2011
DOI: 10.3138/cjwl.23.1.289
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Together or Drifting Apart? Targeting Care Work as “Work Like No Other”

Abstract: L'article décrit la précarité et autres conséquences inattendues que peut entraîner le traitement d'exception du travail domestique en tant que « travail à nul autre pareil », en examinant la controverse causée par le paiement des heures supplémentaires pour les aides familiales résidantes en Israël. Bien que la jurisprudence des tribunaux du travail d'Israël offre un continuum de solutions à la problématique du paiement des heures supplémentaires pour cette catégorie de main-d'œuvre, la manière dont la Cour s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A typical example is the exclusion of domestic workers from the personal scope of occupational health and safety legislation 4 . Domestic workers are also very often excluded from certain provisions of working time regulation such as protections in relation to night work, maximum working time and remuneration for overtime (Albin, 2012;Mundlak and Shamir, 2011). The regulation of wages is another area of disadvantage for domestic workers; in the UK, for example, live-in domestic workers can be exempted from the minimum wage entitlement if they are treated "as family members" (Mullaly and Murphy, 2014).…”
Section: Debating the Regulation Of Domestic Work: "Work Like No Othementioning
confidence: 99%
See 1 more Smart Citation
“…A typical example is the exclusion of domestic workers from the personal scope of occupational health and safety legislation 4 . Domestic workers are also very often excluded from certain provisions of working time regulation such as protections in relation to night work, maximum working time and remuneration for overtime (Albin, 2012;Mundlak and Shamir, 2011). The regulation of wages is another area of disadvantage for domestic workers; in the UK, for example, live-in domestic workers can be exempted from the minimum wage entitlement if they are treated "as family members" (Mullaly and Murphy, 2014).…”
Section: Debating the Regulation Of Domestic Work: "Work Like No Othementioning
confidence: 99%
“…Scholars like Einat Albin and Virginia Mantouvalou argue that separate statutory instruments which take into account the specificities of domestic work are necessary in order to make employment rights meaningful to domestic workers; by merely including domestic workers into the personal scope of generally applicable employment norms, they argue, would not solve the problem because of enforcement difficulties (Albin, 2012;Mantouvalou and Albin, 2012). The counter-argument, however, is that the enactment of special employment instruments for domestic work exacerbates the sector's disadvantage because specially tailored models tend to grant substandard rights and protections (Mundlak and Shamir, 2011;Ramirez Machado, 2003). Domestic work is indeed "work like any other" but making employment law norms fully applicable to this type of work may require adaptations of the generally applicable legislation; as we shall see in the case of Spain, the two approaches are not necessarily mutually exclusive.…”
Section: Investigaciones Feministasmentioning
confidence: 99%
“…A survey of migrant care workers found that they are employed on average 12.7 hours per day, and that most of them remain on call throughout the night (Kav LaOved 2010). The reluctance to limit the care workers' working hours may also be explained by their family-like role and by a 'commodification anxiety' in relation to marketizing and regulating in-home care activities fully, even when undertaken by paid workers (Mundlak and Shamir 2011).…”
Section: Discussion: Care Work Families and Defamilializationmentioning
confidence: 99%
“…In-home care workers in Israel, whether residents or migrants, are covered by every article of protective employment legislation except one: overtime compensation (Mundlak and Shamir 2011). The partial exclusion from overtime compensation in Israel is the result of the Labor Court interpretation and application of Article 30 of the 1951 Hours of Work and Rest Law (HWR), as affirmed by the High Court of Justice (HCJ).…”
Section: Employment Lawmentioning
confidence: 99%
“…To achieve this transformation, such policies have focused on a variety of elements, including the demarcation of specific tasks, setting a minimum wage, delimitation of working hours, and recognition of the specific knowledge required for this work (Blackett, 2011). These initiatives have, however, met with some limitations in their implementation (Calleman, 2011; Mundlak and Shamir, 2011; Smith, 2011; Van Walsum, 2011; Vega Ruiz, 2011).…”
Section: Professionalismmentioning
confidence: 99%